Massage combined with auricular point sticking and pressing therapy for one cases of insomnia and related nursing management (推拿联合耳穴贴压治疗失眠1例护理体会) - WANG Xinyue (王欣悦); MA Xu (马旭); ZHANG Pin (张聘); XU Bing (许冰); TANG Ling (唐玲) (中西医结合护理)
This paper summarized the nursing experience of a patient with insomnia who received a massage combined with auricular point sticking and pressing therapy. Based on the routine nursing interventions, massage technique was applied once a day for 10 days. The patient was taught with the correct method of conducting auricular point sticking and pressing therapy. The patient’s sleep quality was evaluated by Pittsburgh sleep quality index (PSQI) and Athens Insomnia Scale (AIS) daily. After 10 days of intervention, a relief of insomnia was observed in the patient with prolonged sleep time and increased sleep quality. (本文总结1例失眠患者应用推拿联合失眠耳穴贴压的护理体会。在常规护理基础上, 给予患者推拿联合耳穴贴压, 并教会患者正确的耳穴按压方法, 每日进行睡眠评分。经过10 d的干预后, 患者睡眠时间延长, 睡眠质量提升, 失眠症状得到明显缓解。)